Transmission of nominal exchange rate changes to export prices and trade flows and implications for exchange rate policy - Mathias Hoffmann; Oliver Holtemöller (Deutsche Bundesbank, 2009)
We discuss how the welfare ranking of fixed and flexible exchange rate regimes in a New Open Economy Macroeconomics model depends on the interplay between the degree of exchange rate pass-through and the elasticity of substitution between home and foreign goods. We identify combinations of these two parameters for which flexible and for which fixed exchange rates are superior with respect to welfare as measured by a representative household's utility level. We estimate the two parameters for six non-EMU European countries (Czech Republic, Hungary, Poland, Slovakia, Sweden, United Kingdom) using a heterogeneous dynamic panel approach.
Keywords: F41; F31; F14; 330; Elasticity of substitution between home and foreign goods; exchange rate pass-through; exchange rate regime choice; expenditure switching effect; heterogeneous dynamic panel; New Open Economy Macroeconomics; Exchange Rate Pass-Through; Handelbares Gut; Nicht-handelbares Gut; Substitutionselastizität; Wechselkosten; Wechselkurssystem; Wechselkurspolitik; Neue Makroökonomik offener Volkswirtschaften; Wohlfahrtseffekt; Tschechische Republik; Ungarn; Polen; Slowakei; Schweden; Großbritannien